Digital Revolution in Farmer Fields: VarScout Unveils Kenya's Varietal Landscape – The Case of Potato - Gatto, M.; Borus, D.; Malit, J.; Kihiu, E.; Barker, I.; Echessa, L.; Soto-Torres, J.; Meyer, A. (2025)
This paper reports on data collected through VarScout, a digital crowdsourcing tool, to monitor varietal adoption, turnover, seed use, and yields. Key findings for the case of potato in Kenya include: (1) Shangi is the dominant variety, covering 73% of the area, followed by Steven (7%) and Sherekea (6%); (2) the weighted average varietal age is 9.3 years, with newer varieties performing better; (3) 19.5% of farmers use clean seed, with higher adoption in Nakuru (21.5%) compared to Bungoma (1.5%); (4) farmers using clean seed achieve 1.5 t/ha higher yields than those using saved seed. The study demonstrates the utility of VarScout for cost-effective data collection, while highlighting the need for further methodological improvements and ground-truthing. The findings underscore the significant impact of CIP's breeding efforts, with over 50% of the pedigree of key popular varieties linked to CIP's genebank. The paper provides insights to inform seed system interventions and guide future breeding priorities in Kenya.